“i love my smartphone”: a review study of smartphone addiction and related psychological risk factors - Karaaziz, Meryem; Keskindağ, Buse (Journal of Dependence, 2015)
In recent years, smartphones have begun to play an increasingly important role in the lives of many people. Smartphone usage has dramatically increased due to the availability of applications with a variety of purposes, such as internet, telephone, camera/video, and games. While smartphones have made many things easier, they have also brought some difficulties, such as the emergence of smartphone addiction. This review study summarizes the personality traits and psychological risk factors of individuals with smart phone addiction by analyzing their amount of cell phone and internet usage. A survey of the literature suggested that extroverted people are at higher risk of becoming addicted to smartphones than introverted individuals. In addition, people with neurotic personality traits were also found to be at risk for smartphone addiction. Research demonstrating a relationship between narcissistpersonality disorderandhighusage of social networking sites also emphasizes the direct proportion between smartphone addiction and increased risk. Other research has shown a relationship between stress, signs of depression, and anxiety and the increase in frequency of smartphone use.